Linkage Mapping and Identification of Candidate Genes for Cold Tolerance in Rice (Oryza Sativa L.) at the Bud Bursting Stage - Lina Zhang; Fei Wang; Chunhui Liu; Xiaoding Ma; Di Cui; Bing Han; Longzhi Han (Rice)
Abstract Rice is highly sensitive to low temperatures, making cold stress a significant factor limiting its growth, especially during the bud bursting stage. To address this, an RIL population derived from a cross between cold-tolerant and cold-sensitive rice varieties was used to identify nine QTLs linked to cold tolerance under temperatures of 4 ℃, 5 °C, and 6 ℃ using a high-density genetic map. One candidate gene, LOC_Os07g44410, was identified through gene function annotation, haplotype analysis, and qRT-PCR, with two main haplotypes (Hap1 and Hap2) showing distinct phenotypic differences. qRT-PCR analysis showed that the expression level of LOC_Os07g44410 in cold tolerant lines carrying Hap1 was significantly higher than that in cold sensitive lines carrying Hap2. Hap1, associated with greater cold tolerance, was predominant in japonica rice, while Hap2 related to cold sensitive was majority in indica rice. This study offers valuable genetic resources for further research on cold tolerance mechanisms and breeding applications at the bud bursting stage in rice.